2020
DOI: 10.1111/pce.13931
|View full text |Cite
|
Sign up to set email alerts
|

GmLCLs negatively regulate ABA perception and signalling genes in soybean leaf dehydration response

Abstract: The circadian clock allows plants to actively adapt to daily environmental changes through temporal regulation of physiological traits. In response to drought stress, circadian oscillators gate ABA signalling, but the molecular mechanisms remain unknown, especially in crops. Here, we investigated the role of soybean circadian oscillators GmLCLa1, GmLCLa2, GmLCLb1 and GmLCLb2 in leaf water stress response. Under dehydration stress, the GmLCL quadruple mutant had decreased leaf water loss. We found that the dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…CRISPR/cas9 has been successfully employed to characterise soybean drought-responsive genes using knock-down approaches. For example, CRISPR/cas9mediated mutagenesis of soybean circadian rhythm genes (GmLCLs) generated mutant plants with decreased water loss under dehydration stress conditions (Yuan et al, 2021). Interestingly, breeding and genetic transformation methods have successfully delivered improved soybeans that have been tested in laboratory, glasshouse or field conditions and a few of these varieties have also been approved for commercial production.…”
Section: Breeding For Drought-smart Soybeanmentioning
confidence: 99%
“…CRISPR/cas9 has been successfully employed to characterise soybean drought-responsive genes using knock-down approaches. For example, CRISPR/cas9mediated mutagenesis of soybean circadian rhythm genes (GmLCLs) generated mutant plants with decreased water loss under dehydration stress conditions (Yuan et al, 2021). Interestingly, breeding and genetic transformation methods have successfully delivered improved soybeans that have been tested in laboratory, glasshouse or field conditions and a few of these varieties have also been approved for commercial production.…”
Section: Breeding For Drought-smart Soybeanmentioning
confidence: 99%
“…Furthermore, the phase of circadian genes moved to 12 h at DN 16, 20, and 24, and the amplitude significantly changed (Figure S7b,c). It was recently reported that the phase of the circadian oscillator LHY‐CCA1‐LIKE ortholog ( GmLCL ) gene was delayed under drought stress in soybeans [ Glycine max (L.)] (Yuan et al., 2021), which implied that drought stress perturbed the circadian clock and movement of the phase may be a strategy for enabling plant adaptation to drought stress during a specific time.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that CCA1 -like MYB s play important roles in response to diverse stresses ( Lai et al, 2012 ; Li et al, 2019a ; Chen S. et al, 2020 ; Yuan et al, 2021 ). To investigate if GmMYB133 is involved in response to abiotic stresses, its expression pattern was determined under cold, drought, and salt stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we identified 54 soybean CCA1 -like genes by data mining against the soybean genome database ( Bian et al, 2017a ). However, only few soybean CCA1 -like genes have been functionally studied such as GmLHY s, GmLCL s, GmMYB138a , GmMYB176 , and GmMYB177 , which are associated with the regulation of plant height and internode, isoflavonoid accumulation, ABA perception, and signaling pathway, or in response to stresses ( Liao et al, 2008 ; Li et al, 2012 ; Bian et al, 2017a ; Wang et al, 2021 ; Yuan et al, 2021 ). Recently, GmMYB133 was reported to be involved in the regulation of isoflavonoid accumulation ( Bian et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%